Association Between Social Network and Cognitive Function: A Cross-Sectional Assessment From the Cardiovascular and Metabolic Diseases Etiology Research Center Cohort (2013–2018) - Kim, Jimin; Yang, Ji Su; Youm, Yoosik; Kim, Dae Jung; Kim, Hyeon Chang; Jung, Sun Jae (Frontiers in Psychiatry, 2022)
Background This study aimed to investigate how social networks are associated with cognitive function in the middle-aged and elderly Korean community population. Methods A total of 7,704 individuals over the age of 50 were included from the baseline recruitment of the Cardiovascular and Metabolic Diseases Etiology Research Center cohort from the years 2013 to 2018. Egocentric social network characteristics including network size, intimacy, and frequency of face-to-face meetings were measured as exposures, and the Korean version of Mini-Mental State Examination (K-MMSE) score was measured to reflect general cognitive function as an outcome. We also stratified the analysis by income level into tertiles, with income caps of 42,000 thousand won and 72,000 thousand won. A generalized linear regression model was used, adjusting for age, gender, socioeconomic status, lifestyle factors, depressive symptoms, and study settings. Results Social network properties were positively associated with cognitive function in both men and women. However, the specific estimates varied according to gender and income level. In men, frequency was most significantly associated with cognitive function (standardized ß=0.093, p-value<.0001). In women, the strength of the association with cognitive function was found in size (standardized ß=0.055, p-value=0.001). The effect modification of income level could be seen in the association between frequency and cognitive function. The strongest association between frequency and cognitive function was found in the middle income group in men (standardized ß=0.114, p-value=0.0063), and the low income group in women (standardized ß=0.076, p-value=0.0039). Conclusion There were positive associations between social network properties (i.e., size, intimacy, and frequency of face-to-face meetings) and cognitive function. The degree of association varied according to social network properties, gender, and income level. Overall, among social network properties, social network size was an important factor in the cognition of women, whereas frequency was important in the cognition of men.